The usefulness and reliability of fitness testing protocols for ice hockey players: A literature review - Nightingale, S. C.; Miller, S.; Turner, A. (The Journal of Strength and Conditioning Research, 2013)
Ice hockey, like most sports, uses fitness testing to assess athletes. This study reviews the current commonly used fitness testing protocols for ice hockey players, discussing their predictive values and reliability. It also discusses a range of less commonly used measures and limitations in current testing protocols. The article concludes with a proposed testing program suitable for ice hockey players.